A simple weak form for contact problems with Coulomb friction - Tan Tai, Nguyen Huynh; Van Anh, Le (Vietnam Journal of Mechanics, 2011)
This paper proposes a weak form for the contact problem with Coulomb friction, written as extension of the standard virtual work principle and involving both the displacements and the multipliers defined on the reference contact surface. The mixed relationship is shown to be equivalent to the strong form of the initial/boundary value contact problem, and it can be discretized by means of the finite element method in a simple way. Typical numerical examples are given to assess the efficiency of the formulation in statics and dynamics.